HATI DAN KETENANGAN JIWA DALAM PERSPEKTIF I’JAZ TIBBI FI AL-QUR’AN KARYA DR. SAYYID AL-JUMAILI - Khomsa Maulana (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
This article discusses the concept of inner peace from the perspective of I‘jaz Ṭibbi fi ‘Ulum al-Qur’an by Dr. Sayyid Al-Jumaili. The study focuses on the analysis of the heart as the center of spiritual awareness and the controller of human psyche, both biologically and spiritually. This research uses a library research method with thematic interpretation and Islamic psychology approaches. The findings reveal that this book explicitly explains the relationship between the physiological stability of the heart and spiritual peace, as described in the Qur’an and reinforced by modern medical insights. This study highlights the contribution of scientific miraculousness (i‘jaz ṭibbi) in interpreting Qur’anic verses related to the soul and enriches the discourse between revealed knowledge and psychological sciences.Kata Kunci: ketenangan jiwa, hati, i‘jaz ṭibbi, al-Qur’an, Sayyid Al-Jumaili.Abstract is written in one paragraph that includes four things